O que pensam as educadoras e o que nos revelam os bebês sobre a organização dos espaços na educação infantil - Silva, Viviane dos Reis (2018)
This research seeks to understand the teaching knowledge about the organization of spaces for babies and the use of these spaces by children in Early Childhood Education. Our theoretical framework is composed of the works of Abramowicz; Oliveira (2010); Agostinho (2004); Cairuga (2015); Carvalho (2011); Delgado; Müller (2005); Fernandes (2016); Horn (2004; 2015; 2013; 2014); Gandini (1999); Guimarães (2009); Nornberg (2013); Rocha (2008); Simiano e Vasques (2011), Soares; Sarmento; Tomás, (2004) and among other authors who make discussions in the light of the Sociology of Childhood. This is a qualitative research, configured in a case study. The research area investigated was the age group called Nursery I of a municipal nursery, located in Nossa Senhora do Socorro/SE, made up of eight babies and two educators. Data were produced based on participant observation. We carried out observations of nursery routines, followed by field diary writings, video recordings and image records through photographs, interviews with educators and questionnaires. All these procedures allowed for the organization of reflexive meetings with the educators known as Mobiles of Knowledge. Using the autoscopy technique (SADALLA; LAROCCA, 2004) interviews, videotaped shows, episodes described, photos and written records were reviewed, problematizing the organization of spaces where such actions were carried out by the educators and children who are members of the study. The analysis of the data produced was performed using the assumptions of content analysis (BARDIN, 2007). This proposal is based on the construction of a formative research, allowing to establish dialogues between the researcher's and the involved subjects' perspectives, thus contributing to provoke reflections of the professionals who work in the day-care center about their work, being stoned, for through the combination of theory and practice, reflections on pedagogical practices, based on a path that values the quality of spaces built with and for children entering infant education since infants. The data produced reveal that the pedagogical dimension of the organization of the spaces for babies is evidenced by the games, explorations and interactions raised by them. The Mobiles of Knowledge have tried to the necessity of reorganizations and resignifications of such spaces from a close look at the motivations and interests exposed by the babies. Revisiting and reflecting on the moments played by the babies and educators in the different spaces of the nursery led the subjects of this research to value the spatial arrangements that shared experiences, everyday, recognizing them as an important curricular component of the pedagogical practice with babies.